Introgression in the genus Campylobacter: generation and spread of mosaic alleles. - Sheppard, S; McCarthy, N; Jolley, K; Maiden, M (2011)
Horizontal genetic exchange strongly influences the evolution of many bacteria, substantially contributing to difficulties in defining their position in taxonomic groups. In particular, how clusters of related bacterial genotypes - currently classified as microbiological species - evolve and are maintained remains controversial. The nature and magnitude of gene exchange between two closely related (approx. 15 % nucleotide divergence) microbiologically defined species, Campylobacter jejuni and Campylobacter coli, was investigated by the examination of mosaic alleles, those with some ancestry from each population. A total of 1738 alleles from 2953 seven-locus housekeeping gene sequence types (STs) were probabilistically assigned to each species group with the model-based clustering algorithm structure. Alleles with less than 75 % assignment probability to one of the populations were confirmed as mosaics using the structure linkage model. For each of these, the putative source of the recombinant region was determined and the allele was mapped onto a clonalframe genealogy derived from concatenated ST sequences. This enabled the direction and frequency of introgression between the two populations to be established, with 8.3 % of C. coli clade 1 alleles having acquired C. jejuni sequence, compared to 0.5 % for the reciprocal process. Once generated, mosaic genes spread within C. coli clade 1 by a combination of clonal expansion and lateral gene transfer, with some evidence of erosion of the mosaics by reacquisition of C. coli sequence. These observations confirm previous analyses of the exchange of complete housekeeping alleles and extend this work by describing the processes of horizontal gene transfer and subsequent spread within recipient species.